Actors’ perceptions of government performance in support of value chain development in marine small-scale fisheries in Kenya - Kimani, Patrick; Wamukota, Andrew; Manyala, Julius O.; Mlewa, Chrisestom Mwatete (Elsevier, 2020)
Small-scale fisheries actor’s perceptions of government performance in implementing value chain development functions outlined in policies and laws, are inadequately studied. The present study conducted in Malindi, Mayungu, Mombasa, Shimoni and Vanga in Kenya, sought to address this gap. The study gauged actors’ perception of national and county governments’ performance towards value chain development objectives and factors influencing such perceptions. Data was collected through field interviews targeting 403 actors consisting of fishers, middlemen and small-scale processors at five locations. A five-point Likert scale was used in recording actors’ perceptions. Results show that the national government was rated better than county governments. Provision of equipment and promotion of value addition and fish marketing were rated lowest, while promotion of cooperation and community-level management were rated highest. Geographic factors emerged as most important in influencing actors’ perceptions, while economic factors had no significant influence. Although objectives of the policy and Fisheries Act had not been fully realized, recent comprehensive reforms are likely to address identified shortcomings.